Imperial Sovereignty and Local Politics :The Bhaduria Rajputs and the Transition from Mughal to British India, 1600-1900 - Tripurdaman Singh (CUP, 2019)
Imperial Sovereignty and Local Politics takes at its focus the historically significant interconnections between local polities and imperial formations in South Asia. Using the relationship between the Bhadauria Rajputs and the Mughal, Maratha and British Empires as a prism to evaluate the constitution of sovereignty and the process of state formation, it demonstrates the enduring relevance of symbolism and ritual, the persistence of pre-colonial political forms and ideologies and the continuing importance of local power networks in moulding imperial projects. Employing theories of state formation borrowed from anthropology, Singh emphasizes the need to conceptually separate political authority from symbolic sovereignty and examine the local context of imperial politics. This work provides a compelling re-orientation of the way we understand the nature of imperial states, the experience of sovereignty and the processes of political change in the eighteenth and nineteenth centuries.